2008
DOI: 10.1038/bjp.2008.71
|View full text |Cite
|
Sign up to set email alerts
|

Vardenafil protects isolated rat hearts at reperfusion dependent on GC and PKG

Abstract: Background and purpose: The type-5 PDE inhibitor vardenafil reduces myocardial infarct size in situ, following ischemia/ reperfusion, when applied at reperfusion in animal models. Little is known about the underlying protective signaling. Here, we test whether vardenafil is protective in rat isolated hearts and in a cell model of calcium stress. Experimental approach: Infarct size in rat isolated hearts was measured after a 30 min regional ischemia and 120 min reperfusion. Vardenafil (1 nM-1 mM) was infused du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…These results provide a new signaling mechanism underlying the cardioprotective effects of sildenafil and possibly other PDE-5 inhibitors that are currently in use for treatment of ED in men. It is noteworthy that our current results are conceptually supported by a recent study, which demonstrated that another PDE-5 inhibitor, vardenafil, administered at reperfusion in an isolated rat heart model induced cardioprotection against ischemiareperfusion injury through activation of guanylyl cyclase and enhancement of PKG activity (28).…”
Section: Discussionsupporting
confidence: 77%
“…These results provide a new signaling mechanism underlying the cardioprotective effects of sildenafil and possibly other PDE-5 inhibitors that are currently in use for treatment of ED in men. It is noteworthy that our current results are conceptually supported by a recent study, which demonstrated that another PDE-5 inhibitor, vardenafil, administered at reperfusion in an isolated rat heart model induced cardioprotection against ischemiareperfusion injury through activation of guanylyl cyclase and enhancement of PKG activity (28).…”
Section: Discussionsupporting
confidence: 77%
“…In the past several years, there has been considerable attention paid to their potential cardioprotective properties, and indeed, there is a growing body of preclinical evidence to support it. The mechanism of PDE5 cardioprotection is complex and beyond the scope of this review, but PDE5 inhibitors appear to be ischemic preconditioning mimetics (87)(88)(89) as well as inhibitors of MPTP formation (90). Other mechanisms may involve reduction in arterial blood pressure (91), attenuation of inotropic responses to catecholamines (92,93), and nitric oxide signaling (94,95).…”
Section: Promising Therapies For the Futurementioning
confidence: 98%
“…In animal models of myocardial ischaemia and IRI, PDE5i use has reduced infarct size, improved left ventricular performance, suppressed ischaemia-induced arrhythmias and improved animal survival. 12 13 15 28-30 A number of proposed mechanisms for their cardioprotective actions in IRI exist including activation of PKG through the nitric oxide signalling pathway, 31 32 opening of mitochondrial ATP-sensitive potassium channels 28 and stimulation of the sarcolemmal Na+−K+ ATPase pump. 33 In addition to direct myocardial effects, PDE5is may afford protection against endothelial reperfusion injury, 34 improve vascular endothelial function and reduce systemic and pulmonary BP.…”
Section: Comparison With Other Studies and Possible Mechanismsmentioning
confidence: 99%
“…9 This is supported by compelling evidence from animal models indicating that the PDE5is such as sildenafil, tadalafil and vardenafil are cardioprotective in ischaemia-reperfusion injury (IRI) while suppressing cardiac arrhythmias and improving cardiac function. [10][11][12][13][14][15] Furthermore, small randomised controlled trials (RCTs) in systolic heart failure have shown an improvement in haemodynamic parameters and functional indices. 16 It is therefore important to establish whether there is benefit or harm in highrisk patients with ED.…”
mentioning
confidence: 99%